1996
DOI: 10.1515/cclm.1996.34.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Association between Deletion Polymorphism of the Angiotensin-Converting Enzyme Gene and Cerebral Atherosclerosis

Abstract: We investigated deletion polymorphism in the gene for angiotensin-converting enzyme in patients with angiographically verified cerebral atherosclerosis. Genotypes were determined by the polymerase chain reaction with oligonucleotide flanking of the polymorphic region of intron 16 of the angiotensin-converting enzyme gene.Results of angiotensin-converting enzyme genotyping showed 46% of 50 studied patients to be homozygous for the DD allele, whose prevalence was significantly increased as compared with a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Risk factors for ICAD are categorized as nonmodifiable, well documented and modifiable, or less well documented regardless of whether modifiable (Table). 3, 8–38 Most of the studies of risk factors for ICAD were conducted in symptomatic patients. Age, hypertension, and diabetes mellitus are identified as independent risk factors for ICAD 8.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for ICAD are categorized as nonmodifiable, well documented and modifiable, or less well documented regardless of whether modifiable (Table). 3, 8–38 Most of the studies of risk factors for ICAD were conducted in symptomatic patients. Age, hypertension, and diabetes mellitus are identified as independent risk factors for ICAD 8.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Other studies have also suggested that ICAD is more common in men, particularly in younger age groups12, 13 and in particular locations, such as the basilar artery 14. Several studies have demonstrated the relation between ICAD and total serum cholesterol and its various components (see the Table3, 8–38). There are also some preliminary data that ICAD in younger patients affects different anatomic regions and occurs in the absence of atherosclerotic risk factors 39…”
Section: Risk Factorsmentioning
confidence: 99%
“…These include angiotensin converting enzyme polymorphism, plasma to vascular endothelial growth factor ratio, glutathione S-transferase, omega-1 gene polymorphism, and plasma homocysteine level [13,[29][30][31][32]. They exert their action via various mechanisms such as vascular endothelial injury, proliferation of vascular smooth muscle cell, and impairment of angiogenesis.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Multiple genetic factors have been identified that may enhance and promote premature atherosclerosis in the whole vascular system including intracranial large arteries. These include angiotensin converting enzyme polymorphism, plasma to vascular endothelial growth factor ratio, glutathione S-transferase, omega-1 gene polymorphism, and plasma homocysteine level [13,[29][30][31][32]. They exert their action via various mechanisms such as vascular endothelial injury, proliferation of vascular smooth muscle cell, and impairment of angiogenesis.…”
Section: Genetic Factorsmentioning
confidence: 99%